Penguasaan Kosakata Bahasa Indonesia Siswa Kelas I di UPT SDN 1 Bangkala Barat Kabupaten jeneponto: Indonesian Vocabulary Mastery of Grade I Students at UPT SDN 1 Bangkala Barat, Jeneponto Regency - Nopiyanti, Nopiyanti; Asia M, Asia M; Azis (Journal Studies in Indonesian Language and Literature, 2025)
This study aims to describe the mastery of Indonesian language comprehension in grade I at UPT SDN 1 Bangkala Barat. The type of research used is quantitative descriptive research. The sample in this study was 22 grade I students at UPT SDN 1 Bangkala Barat, Jeneponto Regency, which were obtained using purposive sampling techniques from the population of this study, which amounted to 122 people. The focus of this study is the mastery of Indonesian language comprehension consisting of nouns, verbs, adjectives, and conjunctions in grade I students at UPT SDN 1 Bangkala Barat, Jeneponto Regency. The data collection technique in this study used a questionnaire as the main instrument in data collection. The data analysis technique used in this study was a data analysis technique in the form of descriptive statistics. The results of this study revealed that the highest mastery of Indonesian vocabulary of first-grade students at UPT SDN 1 Bangkala Barat, Jeneponto Regency was in the adjective category, where 13 students (59.1%) were classified as very good. In the verb category, 9 students (40.9%) were classified as very good, but the same number were also classified as poor. Meanwhile, mastery of nouns was classified as quite good with 8 students (36.4%) in the very good category. Meanwhile, mastery of conjunctions showed the lowest results, with 14 students (63.6%) classified as poor and none were classified as very good. This study shows significant variation in vocabulary mastery between categories in first-grade students at UPT SDN 1 Bangkala Barat, Jeneponto Regency. Penelitian ini bertujuan untuk mendeskripsikan penguasaan kosakata bahasa Indonesia kelas I di UPT SDN 1 Bangkala Barat Kabu. Jenis penelitian yang digunakan adalah jenis penelitian deskriptif kuantitatif. Sampel dalam penelitian ini adalah 22 siswa kelas I di UPT SDN 1 Bangkala Barat Kabupaten Jeneponto yang diperoleh menggunakan teknik purposIe sampling dari populasi penelitian ini yang berjumlah 122 orang. Fokus penelitian ini adalah penguasaan kosakata bahasa Indonesia yang terdiri dari kata benda, kata kerja, kata sifat, dan kata hubung pada siswa kelas I di UPT SDN 1 Bangkala Barat Kabupaten Jeneponto. Teknik pengumpulan data dalam penelitian ini menggunakan angket sebagai instrumen utama dalam pengumpulan data.Teknik analisis data yang digunakan dalam penelitian ini adalah teknik analisis data berupa statistik deskriptif. Hasil penelitian ini mengungkapkan bahwa penguasaan kosakata Bahasa Indonesia siswa kelas I di UPT SDN 1 Bangkala Barat Kabupaten Jeneponto paling tinggi terdapat pada kategori kata sifat, dimana 13 siswa (59,1%) tergolong sangat baik. Pada kategori kata kerja, 9 siswa (40,9%) tergolong sangat baik, namun jumlah yang sama juga tergolong kurang. Sementara itu, penguasaan kata benda tergolong cukup baik dengan 8 siswa (36,4%) berada pada kategori sangat baik. Adapun penguasaan kata hubung menunjukkan hasil paling rendah, dengan 14 siswa (63,6%) tergolong kurang dan tidak ada yang tergolong sangat baik. Penelitian ini menunjukkan adanya variasi signifikan dalam penguasaan kosakata antar kategori pada siswa kelas 1 di UPT SDN 1 Bangkala Barat Kabupaten Jeneponto